Refugee family reunion: What might have been. (September 2018) - Taylor, Savitri
This article demonstrates that many refugees in Australia are deliberately denied a realistic prospect of achieving family reunion. It then explains why, in cases not involving child refugees in Australia, Australia has significant room to deny any international obligation to enable refugee family reunion. Finally, it discusses what might have been, if international legal history had played out a little differently.